Molecular identification of Wolbachia and Sodalis glossinidius in the midgut of Glossina fuscipes quanzensis from the Democratic Republic of Congo - Simo Gustave; Kanté Sartrien Tagueu; Madinga Joule; Kame Ginette; Farikou Oumarou; Ilombe Gillon; Geiger Anne; Lutumba Pascal; Njiokou Flobert (Parasite, 2019)
During the last 30 years, investigations on the microbiome of different tsetse species have generated substantial data on the bacterial flora of these cyclical vectors of African trypanosomes, with the overarching goal of improving the control of trypanosomiases. It is in this context that the presence of Wolbachia and Sodalis glossinidius was studied in wild populations of Glossina fuscipes quanzensis from the Democratic Republic of Congo. Tsetse flies were captured with pyramidal traps. Of the 700 Glossina f. quanzensis captured, 360 were dissected and their midguts collected and analyzed. Sodalis glossinidius and Wolbachia were identified by PCR. The Wolbachia-positive samples were genetically characterized with five molecular markers. PCR revealed 84.78% and 15.55% midguts infected by Wolbachia and S. glossinidius, respectively. The infection rates varied according to capture sites. Of the five molecular markers used to characterize Wolbachia, only the fructose bis-phosphate aldolase gene was amplified for about 60% of midguts previously found with Wolbachia infections. The sequencing results confirmed the presence of Wolbachia and revealed the presence of S. glossinidius in the midgut of Glossina f. quanzensis. A low level of midguts were naturally co-infected by both bacteria. The data generated in this study open a framework for investigations aimed at understanding the contribution of these symbiotic microorganisms to the vectorial competence of Glossina fuscipes quanzensis.